Designing a Village Information System Through Social Media Schemes and Website Prototypes in Trimulyo Village, Yogyakarta - Bhakti Gusti Walinegoro; Herpita Wahyuni; Sakir Sakir (Universitas Serang Raya, 2022)
This study aims to analyze the implementation of the University of Muhammadiyah Yogyakarta Real Work Lecture (KKN) program based on Information Technology (IT) by designing a village information system through the creation of social media designs and the design of the Trimulyo Kallurahan website prototype. Kaluarahan Trimulyo does not yet have a profile book, and social media displays do not yet have an attractive design. The implementation of community empowerment through the University of Muhammadiyah Yogyakarta Real Work Lecture program based on Kalurahan Online (Kaline) is supported by creating a village profile that provides information on the village, population, and village potential. Making website prototype designs and social media display designs are beneficial in digitizing progress and services in Trimulyo Village. The social media display method and the prototype design of the Trimulyo Village Website are the first steps in optimizing the Website and Social Media in Trimulyo Village.